Micronutrient nutrition in sugarcane: a brief review - Rodrigues da Silva, Luiz Daniel; Ferreira de Lima Cruz, José Manoel (Scientia Agraria Paranaensis, 2021)
Sugarcane is a crop of worldwide economic value used in sugar, electricity, and alcohol production. This review demonstrates the importance of the main micronutrients and their respective effects on the development and yield of sugarcane. Micronutrient deficiency is one of the limiting factors in sugarcane productivity in producing regions. This deficit is related to several aspects, such as fertilizer use with low micronutrient levels, increased agricultural productivity, and decreased productivity levels of soil organic matter. Thus, proper fertilization management can circumvent the limiting factors such as the foliar application of boron and soil fertilization of zinc, both resulting in greater stem production. Molybdenum increases biological nitrogen fixation in sugarcane and contributes to the accumulation of N in the plant. Iron and manganese are involved in chlorophyll content and dry matter accumulation in sugarcane. In this review, we show the contributions of fertilization with microelements to the development of the sugarcane sector. In this perspective, more research is needed on micronutrient fertilization to increase sugarcane productivity in different soil and climate conditions.